Sintering technology - German, Randall M.; Messing, Gary L; Cornwall, Robert G. (Marcel Dekker, 1996)
Based on the sintering conference held at the Pennsylvania State University, USA, this text presents advances in the application of sintering to the important industrial materials. It offers results on both solid-state and microphase sintering as well as microstructure evolution. It introduces applications and processes to technical problems.